Rare Case of Cocaine-Induced Aortic Aneurysm: A Near Dissection Event - Ranju Kunwor; AnnMarie Canelas (Case Reports in Cardiology)
Cocaine use has been associated with cardiovascular complications such as coronary atherosclerosis, coronary artery spasm, cardiac arrhythmias, acute myocardial infarction, myocarditis, and dilated cardiomyopathies. Aortic dissection is a rare but life-threatening complication of cocaine use. Cocaine and stimulant use can cause aortic aneurysm by increasing the aortic wall stress, and the most feared complications are dissection, rupture, and death. There are no clear guidelines about screening cocaine abusers with CT scan of the chest. We do not know if the number of years of cocaine use or the amount of cocaine use can be associated with higher incidence of aortic aneurysm or dissection. Cocaine-induced aortic aneurysm does not have any specific clinical feature. Common presentation is chest discomfort or chest pain. This common presentation is bewildering enough for clinicians to think of more common causes of chest pain like myocardial infarction and myocarditis. The sudden onset of severe, sharp, stabbing chest or back pain is suggestive of aortic dissection. Here, we present a young otherwise healthy patient with chronic cocaine use presenting with chest pain and found to have significant size aortic aneurysm.